MICROENCAPSULATION OF KARAMUNTING LEAF EXTRACT (Rhodomyrtus tomentosa) AS AN INSTANT DRINK POWDER - Supriyono, Teguh; Sera, Agnescia Clarissa (Proceedings of the International Conference on Applied Science and Health, 2019)
Backgrounds: Karamunting (Rhodomyrtus tomentosa), a local wild plant from Central Kalimantan, Indonesia is believed by the Dayak tribe to treat diabetes mellitus. Based on the literature review, there have been no studies related to Karamunting focused on processed products in practical dosage forms in the form of instant powder, which has the longest shelf life. This study aims to explore the solubility and percentage of insoluble solids of Karamunting leaf powder that has been encapsulated with the addition of Maltodextrin. In addition, an assessment of the sensory attributes of Karamunting leaf drinks was also carried out. Methods: This study was used an experimental with applied the Randomized Block Design (RBD) design with 2 factors, comparing the number of Karamuting leaf extracts and the concentration of Maltodextrin to produce a formula of 0.5L:5%, 0.5L:10%, 0.5L:15%, 1L:5%, 1L:10% and 1L:15%. This research conducted in the Laboratory of Agricultural Product Technology, Gadjah Mada University, Yogyakarta, Indonesia from November to December 2018. Results: The application of spray dryer produced fine powder of Karamunting drink. It has a distinctive aroma and its color was ranged from bright cream to slightly brownish. Addition of Maltodextrin significantly accelerated powder?s solubility and decreased its yield (p<0.05). Panelists tend to prefer products with 1 L of Karamunting leaf extract and 10% Maltodextrin. Conclusions: Solubility rate of Karamunting leaf extract is strongly influenced by the concentration of Maltodextrin. The higher the concentration of Maltodextrin, the faster the product will be dissolved. Addition of Maltodextrin significantly reduced the total of insoluble solids. However, antidiuretic activity of Karamunting drink should be investigated to prove its health claim.